2007
DOI: 10.1104/pp.106.090241
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Profiling in Tomato Reveals a Role for Glycosyltransferase in Mi-Mediated Nematode Resistance

Abstract: Root-knot nematode (RKN; Meloidogyne spp.) is a major crop pathogen worldwide. Effective resistance exists for a few plant species, including that conditioned by Mi in tomato (Solanum lycopersicum). We interrogated the root transcriptome of the resistant (Mi1) and susceptible (Mi-) cultivars 'Motelle' and 'Moneymaker,' respectively, during a time-course infection by the Mi-susceptible RKN species Meloidogyne incognita and the Mi-resistant species Meloidogyne hapla. In the absence of RKN infection, only a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 66 publications
(85 reference statements)
4
66
0
4
Order By: Relevance
“…Jaubert et al (2005) reported a molecule Mi-CRT, localized at the tip of the nematode stylet, and at the cell wall of the GCs, supporting oesophageal molecule insertion during the establishment of NFS. Similar studies identified different candidate molecules from oesophageal gland of M. incognita (Huang et al 2005;Mitreva-Dautova et al 2006;Schaff et al 2007). Authors speculated that those molecules could be acting as a facilitator of entering and intercellular movement of the RKN at the early phases of the parasitism.…”
Section: Molecular Mechanism Of Establishing Nematode-induced Feedingmentioning
confidence: 82%
See 3 more Smart Citations
“…Jaubert et al (2005) reported a molecule Mi-CRT, localized at the tip of the nematode stylet, and at the cell wall of the GCs, supporting oesophageal molecule insertion during the establishment of NFS. Similar studies identified different candidate molecules from oesophageal gland of M. incognita (Huang et al 2005;Mitreva-Dautova et al 2006;Schaff et al 2007). Authors speculated that those molecules could be acting as a facilitator of entering and intercellular movement of the RKN at the early phases of the parasitism.…”
Section: Molecular Mechanism Of Establishing Nematode-induced Feedingmentioning
confidence: 82%
“…Those resistance genes are commercially used in tomato breeding programs in controlling three main RKN species, M. (Schaff et al 2007). On the other hand, callose or lignin synthesis at plant cell wall acts as a physical barrier of stylet penetration in where glycosyltransferases genes may play a role in cell wall synthesis reported by Egelund et al (2004).…”
Section: Natural Resistance Gene In Controlling Rknmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in spotting technology now routinely allow up to 30,000 cDNA fragments to be spotted on a single chip. These cDNA chips are routinely created in research labs and used for specific studies (Alkharouf et al 2006 ;Khan et al 2004 ;Schaff et al 2007) . However, the use of cDNA microarrays has been somewhat problematic due to potential errors caused by cross-hybridization and/or nonuniformity of hybridization as the result of the presence of palindromes or homopolymeric runs.…”
Section: Microarray Analyses Of Plant-nematode Interactionsmentioning
confidence: 99%